Stress and strain distribution in femoral heads for hip resurfacing arthroplasty with different materials: A finite element analysis. (January 2021) - Vogel, Danny; Wehmeyer, Merle; Kebbach, Maeruan; Heyer, Horst; Bader, Rainer
Abstract: Femoral bone loss due to stress and strain shielding is a common problem in hip resurfacing arthroplasty (HRA), which arises from the different stiffness of implant materials and the adjacent bone. Usually, the implants used in HRA are made of cobalt-chromium alloy (CoCr). As a novel concept, implants may also be made of ceramics, whose stiffness exceeds that of the adjacent bone by a multiple. Therefore, this computational study aimed to evaluate whether poly (ether-ether-ketone) (PEEK) or a hybrid material with a PEEK body and ceramic surface made of alumina toughened zirconia (ATZ) might be more suitable implant alternatives for HRA, as they can avoid stress and strain shielding. A reconstructed model of a human femur with an HRA implant was simulated, whereby the material of the HRA was varied between CoCr, ATZ, zirconia toughened alumina (ZTA), PEEK, and a hybrid PEEK-ATZ material. The implant fixation method also varied (cemented or cementless). The simulated models were compared with an intact model to analyze stress and strain distribution in the femoral head and neck. The strain distribution was evaluated at a total of 30, 344 (cemented HRA) and 63, 531 (uncemented HRA) nodes in the femoral head and neck region and divided into different strain regions (<400 µm/m: atrophy; 400–3000 μm/m: bone preserving and building; 3000–20, 000 μm/m: yielding and >20, 000 μm/m fracture). In addition, the mechanical stability of the implants was evaluated. When the material of the HRA implant was simulated as metal or ceramic while evaluating the strains, it was seen that around 22–26% of the analyzed nodes in the femoral head and neck were in an atrophic region, 47–51% were in a preserving or building region, and 27–28% were in a yielding region. In the case of PEEK implant, less than 0.5% of the analyzed nodes were in an atrophic region, 66–69% in a preserving or building region, and 31–34% in a yielding region. The fixation technique also had a small influence. When a hybrid HRA was simulated, the strains at the analyzed nodes depended on the thickness of the ceramic material. In conclusion, the material of the HRA implant was crucial in terms of stress and strain distribution in the adjacent bone. HRA made of PEEK or a hybrid material leads to decisively reduced stress and strain alteration compared to stiffer materials such as CoCr, ATZ, and ZTA. This confirms the potential for reduction in stress and strain shielding in the femoral head with the use of a hybrid material with a PEEK body for HRA.